Influence of Ionic Strength and Temperature on the Adsorption of Reactive Black 5 Dye by Activated Carbon: Kinetics, Mechanisms and Thermodynamics - Mario Cetina; Petra Mihovilović; Ana Pešić; Branka Vojnović (Molecules, 2025)
The aim of this work was to investigate the influence of ionic strength and temperature on the adsorption of Reactive Black 5 dye on commercial powdered activated carbon. Adsorption experiments were performed at 45 °C with the addition of NaCl (c0 = 0.01, 0.05, 0.10 and 1.00 M) and Na2SO4 (c0 = 0.01 M). The results were compared with those obtained for both salts (c0 = 0.01 M) at three additional temperatures: 25, 35 and 55 °C. For all adsorption experiments, kinetic and thermodynamic studies were performed. This research showed that the addition of NaCl, even in the concentration of only c0 = 0.01 M, significantly enhanced dye adsorption and that higher NaCl concentration resulted in higher adsorption capacity. In addition, slightly higher adsorption was observed when Na2SO4 was added to the dye solution at the same concentration as NaCl, as well as at a higher temperature, regardless of the salt added to the dye solution. It was also shown that adsorption is kinetically controlled, assuming a pseudo-second-order model, and that intraparticle diffusion is not the only process that influences the adsorption rate. Finally, calculated thermodynamic parameter values for both salts (c0 = 0.01 M) indicate that adsorption was a spontaneous endothermic process.